Introduction. Cultural Research in/of the Kitchen Tracks and Meanings (In the Kitchen. Cultural Sketches on Space, 2019)
The authors present the idea of a publication entitled In the Kitchen. Cultural Sketches about Space. They assume that the kitchen is a room associated with many cultural and social meanings. It is primarily an inalienable part of the home, private, inhabited space that can be variously designated, organized and experienced. The kitchen usually performs activities and processes related to meal planning, storage and processing of products as well as preparation and consumption of food. There are various practices inherent in the cultural reflection on lifestyles, corporality and gender, which are an emanation of social change and an attempt to (re)define tradition and identity. The space of the kitchen is a subject to fashions, trends and ideologies, aesthetic and economic rules. The authors, along with other researchers in this publication, do not present a consistent history of changes that affect the kitchen. They try to show a space full of meanings on selected examples, reaching to different cultural and social contexts.